Determinan Kepatuhan Minum Obat Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Lubuk Begalung Kota Padang Tahun 2024 - Yasri, Fadila; Asyari, Dian Paramitha (JUKEJ : Jurnal Kesehatan Jompa, 2024)
Prevalence of Hypertension among Individuals Aged > 15 Years in Padang Reached 22.4% in 2022.The objectives of this study are to determine: (1) the frequency distribution of medication adherence among hypertensive patients, (2) the frequency distribution of knowledge among hypertensive patients, (3) the frequency distribution of attitudes among hypertensive patients, (4) the frequency distribution of family support for hypertensive patients, (5) the relationship between knowledge and the incidence of hypertension among hypertensive patients, (6) the relationship between attitude and the incidence of hypertension among hypertensive patients, and (7) the relationship between family support and the incidence of hypertension among hypertensive patients in the Lubuk Begalung Community Health Center (Puskesmas) area. This quantitative study employs a cross-sectional design. The research is conducted in the Lubuk Begalung Community Health Center area in Padang in 2024. The population for this study consists of all hypertensive patients in the Lubuk Begalung Puskesmas area in 2023, totaling 651 individuals, with a sample size of 87 individuals. Analysis methods include univariate and bivariate analysis using the chi-square test. The study results indicate that hypertensive patients in the Lubuk Begalung Puskesmas area show poor adherence to medication. Of the respondents, 65 individuals (74.7%) have low knowledge about hypertension, 71 individuals (81.6%) exhibit negative attitudes toward hypertension, and 49 individuals (56.3%) receive inadequate family support. Bivariate analysis reveals significant relationships between knowledge and medication adherence (p-value 0.009), attitude and medication adherence (p-value 0.011), and family support and medication adherence (p-value 0.008). Conclusion: The Puskesmas should promote health education about the importance of medication adherence for hypertension to enhance the health and well-being of hypertensive patients, enabling early prevention, reducing complications, and avoiding relapses and mortality among hypertensive patients, ultimately improving recovery rates. Keywords: Adherence, knowledge, attitude, and family support.